Influence of the bioturbator Upogebia cf. pusilla on trace metal remobilization: Does parasitism matter?. (August 2018) - Dairain, Annabelle; de Montaudouin, Xavier; Gonzalez, Patrice; Ciutat, Aurélie; Baudrimont, Magalie; Maire, Olivier; Gourves, Pierre-Yves; Daffe, Guillemine; Legeay, Alexia
Abstract: Marine sediments are an important source of contaminants since they are susceptible to be remobilized to the water column. By modifying the physical and biogeochemical characteristics of sediments, bioturbation can influence contaminants remobilization. Within bioturbators, mud shrimp are considered as among the most influential organisms in marine soft-bottom environments. The physiological state of mud shrimp can be impaired by bopyrid parasites. The present study aims to evaluate the influence of bopyrid-uninfested and bopyrid-infested mud shrimp on sediment contaminants resuspension. Through a 14-days ex-situ experiment we showed a moderate effect of mud shrimp on contaminant remobilization compared to molecular diffusion without the bioturbator. Conversely, parasite presence significantly impaired contaminant bioaccumulation in mud shrimp and interfered with genetic expression. The weak effect of mud shrimp on contaminant remobilization may be due to trace metal accumulation and thus we suggested to evaluate the influence of contaminants on activities of bioturbating species. Highlights: Impact of bioturbation and parasitism on the fate of Cd in the sediment was studied. Release of Cd in the water column was mainly due to molecular diffusion. Bioturbating organisms exhibited significant Cd bioaccumulation. Parasitism interfered with Cd bioaccumulation process. Parasitism and Cd interfered with genetic expression.